A Jewish Response - Cohn-Sherbok, Dan (Journal for the study of religion, nature and culture, 2000)
Bret Stephenson and Susan Power Bratton’s discussion is a fascinating study of Luther’s anti-Jewish views. While it is widely recognized that Luther condemned the Jews and sought to expel them from German lands, little has been written about the ecotheological implications of his attitudes. Stephenson and Bratton’s exploration of the theological model adopted by Luther adds an important dimension to the discussion of Luther’s critique of the Jewish people.